2023
DOI: 10.1097/md.0000000000033464
|View full text |Cite
|
Sign up to set email alerts
|

Progressive muscle relaxation exercises in patients with COVID-19: Systematic review and meta-analysis

Abstract: Background: Patients with COVID-19 will experience high levels of anxiety and depression and poor levels of sleep and quality of life (QoL) due to isolation treatment and uncertain outcomes. Progressive muscle relaxation (PMR) exercises show promising treatment effects on mental health and sleep problems and overall QoL in COVID-19 patients. This study aimed to evaluate the efficacy and safety of PMR exercises in patients with COVID-19. Methods: Both experimental and non-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, our study represents the first investigation into the effects of PMR on sleep quality and anxiety levels among healthcare professionals in isolated environments. PMR can help balance the sympathetic nervous system by promoting relaxation of the body, stimulating blood circulation, and ensuring muscle relaxation ( Ferendiuk et al, 2019 ; Seid et al, 2023 ). Ozgundondu and Gok Metin (2019) and Gallego-Gómez et al (2020) reported the effectiveness of PMR in alleviating anxiety-related sleep disturbances in critical care nurses and nursing students, respectively, leading to improved academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our study represents the first investigation into the effects of PMR on sleep quality and anxiety levels among healthcare professionals in isolated environments. PMR can help balance the sympathetic nervous system by promoting relaxation of the body, stimulating blood circulation, and ensuring muscle relaxation ( Ferendiuk et al, 2019 ; Seid et al, 2023 ). Ozgundondu and Gok Metin (2019) and Gallego-Gómez et al (2020) reported the effectiveness of PMR in alleviating anxiety-related sleep disturbances in critical care nurses and nursing students, respectively, leading to improved academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…PMR were found to be effective in improving sleep quality and reduce anxiety levels in patients with fractures, chronic obstructive pulmonary disease, malignancy, and chronic pain ( Xie et al, 2016 ; Qaseem et al, 2017 ; Seyedi Chegeni et al, 2018 ; Wang et al, 2024 ). In patients with COVID-19, PMR has also demonstrated benefits in ameliorating sleep quality, anxiety, depression, disease severity, and overall quality of life ( Seid et al, 2023 ). Liu et al investigated the effects of PMR administered for 30 min per day for 5 consecutive days on COVID-19 patients in isolation wards, which showed a significant reduction in anxiety levels and improvement in sleep quality in the intervention group ( n = 25) compared to the control group ( n = 26) post-intervention ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is especially crucial for medical students, who often face continuous stress and fatigue, potentially leading to a decline in their coping abilities over time (Andolhe et al, 2015 ). By offering a method to alleviate negative emotions such as fear, anger, and tension, PMR not only enhances individual emotional health but also positively impacts the dynamics and quality of interpersonal relationships (Baldacchino and Draper, 2001 ; Xiao et al, 2020 ; Seid et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…42 It was considered that the decrease in stress levels with PMR application had a positive effect on sleep quality. Moreover, studies that have been conducted using participants with multiple sclerosis, 43 participants diagnosed with chronic obstructive pulmonary disease, 22 and participants with coronavirus disease 2019 26,32 have shown that PMR has positive and curative effects on sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…18 Insufficient sleep leads to tiredness and decreased energy levels. 9 It has been reported that PMR has a healing effect on fatigue [19][20][21][22] and poor sleep quality, [23][24][25][26] which are common symptoms in the postmenopausal period.…”
mentioning
confidence: 99%